Virus-diseased Ulmus laevis in Eastern Germany - Bandte, M.=700 1 Eáing, M.; Obermeier, C.; Buttner, C.
(Es, En)
ilus., 14 ref.
Keywords: ULMUS; VIRUS; SINTOMAS; TRANSMISION DE ENFERMEDADES; CHENOPODIUM; ALEMANIA; OLMO